Skin care habits of patients with eczema at Kiambu Level 5 Hospital, Kiambu county, Kenya: A retrospective cross-sectional studyCapsule Summary - Winnie Njenga, MBChB, MSc; Magoma Mwancha-Kwasa, MBChB, MPH; Kinara Fossa, MSc; Prabhjot Kaur Juttla, BSc; Fredrick Kimani, BSc; Winfred Mwikya, Dip; Francis Makokha, PhD; Hannah Wanyika, MBChB, PhD (Elsevier, 2024)
Background: There is a dearth of data on eczema from the African continent despite the purported increasing burden. Objectives: To describe the prevalence of eczema at Kiambu Level 5 Hospital and patient skincare. Methods: A descriptive retrospective cross-sectional research design was performed describing the period between 2016 and 2020. Data analysis was done using STATA Version 13. Geospatial mapping of patient residence was also conducted. Results: Eczema was the most common skin condition diagnosed with a prevalence of 25.5%. Majority of the patients favored the use of non-conventional products such as bar soap and milking jelly as routine skincare products. Geospatial mapping demonstrated a higher prevalence of eczema in the urban areas and also revealed access to a specialist as a contributor to health-seeking behavior. Limitations: Subtypes of eczema were not described and this data only reflects 1 facility serving an entire county. Conclusion: The prevalence of eczema in Kiambu Level 5 Hospital mirrors the increasing global burden of eczema. Urban environments have a higher density of eczema in Kiambu. More research is needed to decipher the impact of the preferred non-conventional skin care products on eczema.